The diabetic mother’s child is the newborn baby of peculiar risk requiring intensified nursing care during the perinatal period - Grącka, Barbara; Skotnicka-Klonowicz, Grażyna (Nursing Problems / Problemy Pielęgniarstwa, 2013)
The most common pathologies of newborns of diabetic mothers are various and become apparent in: macrosomia, birth defects, biochemical disturbances (hypoglycemia, hypocalcemia, polycythemia, hyperbilirubinemia), perinatal hypoxia, breathing troubles and perinatal injuries makes them a group of special risk, requiring intensified observation and specialized care provided by appropriately trained and experienced nursing staff. The article discusses the different forms of pathologies seen in newborn babies of diabetic mothers, paying particular attention to disease symptoms and a course of action of nursing in particular cases, and also proposes a standard for the treatment of newborns of diabetic mothers. Nursing Topics 2013; 21 (1): 108–116